Implementation Of Augmented Reality As A Daihatsu Terios R Promotion Media Information System Using 3D Unity (Case Study of PT Tunas Mobilindo Perkasa Bandung): Implementation Of Augmented Reality As A Daihatsu Terios R Promotion Media Information System Using 3D Unity (Case Study of PT Tunas Mobilindo Perkasa Bandung) - Willy Prihartono; Muhamad Furqon (Institute of Computer Science (IOCS), 2020)
Augment Reality (AR) is a technology which combines the virtual world with the real world. The use of AR technology is widely used in the fields of education, military, entertainment and advertising. Generally applications that implement AR technology aim to provide information to users more clearly, in real time and interactively. PT Tunas Mobilindo Perkasa is a business engaged in the promotion of sales of four-wheeled vehicles, one of which is located on Jl. Ahmad Yani No. 229-231 Bandung. PT. Tunas Mobilindo Perkasa did a promotion for the sale of four-wheeled vehicles, employees still came to the buyers and offered brochures, for some people who might be interested in buying it, the brochure would be stored for future buyers needing information about the sale, but for some others maybe the brochure will be thrown away and become trash. Therefore PT.Tunas Mobolindo Perkasa applies Augment Reality (AR) to be able to help in promotion and increase sales.